La comunicación publicitaria en la reactivación económica en época de pandemia en los comerciantes de Quevedo del año 2020 - Peñarrieta Bermeo, Gabriela Daniela (2021)
This case study analyzed the incidence of social networks as advertising communication media by entrepreneurs from the Quevedo Canton. It was carried out in order to determine the importance of these social platforms in people's lives. For the successful search for information, this work included a qualitative investigation. A field study was carried out on 3 entrepreneurs to know in depth what was the handling they gave to social networks when they advertised their products or services. To understand the advertising area, our entrepreneurs were asked before, during and after the quarantine. With the project concluded, it was possible to deduce that social networks, in addition to being communication media, are feasible channels for the advertising of ventures. Together they were able to obtain recommendations regarding a better use for the benefit of future and current entrepreneurs at the time of making their advertisements.